Comparative Analysis of Antioxidant Compounds and Antioxidant Activities in Vitro of Different Kiwifruit Juice - Ruijuan LI; Jin LIANG; Dan WANG; Tianzi HUANG; Lu ZHANG; Shuxia YANG; Anwei LUO (Shipin gongye ke-ji, 2022)
Twelve varieties of kiwifruit from the three major lines of Meiwei, Zhonghua and Ruanzao from the two main producing areas of Shaanxi and Sichuan provinces were used as test materials. The main antioxidant active substances, polyphenols, flavonoids, VC, and the content of monomer phenols in fruit were determined. The antioxidant activity in vitro was compared, and the correlation analysis between the antioxidant activity and the antioxidant capacity of fruit juice was carried out, and the varieties with high antioxidant content and strong antioxidant activity were screened out. Results showed that there were significant differences in the antioxidant activity content and antioxidant capacity of different varieties of kiwifruit (P<0.05). The content of VC varied greatly among different varieties, ranging from 27.300 to 130.380 mg/100 g. The content of flavonoids in two varieties of Ruanzao (Yiyu and Lvmi) was significantly higher than that of other varieties (P<0.05). Protocatechin, catechin, chlorogenic acid, and epicatechin were the main polyphenol compounds in kiwifruit. Hongyang, Cuixiang, Yate, and Huayou had strong scavenging ability on DPPH· and ABTS+·, while Yiyu and Lvmi had strong scavenging ability and total reducing power on ·OH. The content of polyphenols in each kiwifruit had a significant correlation with the total reducing power (P<0.05), and there were also correlations between the content of monophenols, and between monophenols and antioxidant activity. According to cluster analysis based on antioxidant activity, twelve varieties of kiwifruit could be divided into six categories. Comprehensive analysis showed that among the 12 varieties, Ruanzao had the strongest antioxidant activity. The research results would provide a scientific basis for the selection of kiwifruit varieties with high antioxidant activity during fresh food and processing.